Improving the accuracy of predicting protein–ligand binding-free energy with semiempirical quantum chemistry charge. (25th February 2019) - Peng, Cheng; Wang, Jinan; Yu, Yuqi; Wang, Guimin; Chen, Zhaoqiang; Xu, Zhijian; Cai, Tingting; Shao, Qiang; Shi, Jiye; Zhu, Weiliang
Aim: It is a challenge to predict binding-free energy (Δ G ) accurately.Methodology/results: For accurate Δ G prediction, a new strategy combining solvated interaction energy (SIE) or molecular mechanics/generalized Born surface area (MM/GBSA) approach with the Coulson charge of both protein and ligand calculated by semiempirical quantum mechanics (SQM), named SIE-SQMPC or MM/GBSA-SQMPC approach, was developed and tested on 50 protein–ligand complexes. Both approaches achieved higher correlation ( R 2 ) between experimental and predicted Δ G than that with Amber-ff03 charge, even for ligands with highly different scaffolds. But, SIE-SQMPC is computationally much faster than MM/GBSA-SQMPC.Conclusion: SIE-SQMPC provided an effective alternative to predict Δ G of protein–ligand binding ( R 2  = 0.66–0.94 for SIE-AM1; R 2  = 0.59–0.98 for SIE-PM7), which has the potential of high-throughput processing for molecular docking and drug design. Graphical abstract: